Pengaruh penambahan ekstrak bawang merah dalam pengencer Ringer’s Dextrose terhadap kualitas sperma Gallus domesticus pada suhu 5°C - Sakinato Mazidda; Suyadi Suyadi; Dyah Hikmawati; Alditya Putri Yulinarsari (Politeknik Negeri Jember, 2022)
Gallus domesticus is a local chicken of Indonesia which should be preserved as a local genetic resource because it has the advantage of high adaptability environment and has an economic value. This study aimed to determine the quality of Gallus domesticus semen the effect of storage time by the addition of Allium cepa extract (ACE) in the Ringer's Dextrose diluent at temperatur of 5°C. The making of Allium cepa extract was done by using the maceration and Gallus domesticus semen was collected using the female teaser method. The collected semen was divided into 4 treatments, T0 (Ringer's Dextrose without ACE); T1 (Ringer's Dextrose + 0.02 ml ACE); T2 (Ringer's Dextrose + 0.04 ml of ACE); T3 (Ringer's Dextrose + 0.06 ml of ACE) and evaluation of the semen quality including individual motility, viability, and abnormality was observed within 6, 8, and 24 hours. The experimental design used a Completely Randomized Design, which proceeded with the Duncan Multiple Range Test. The analysis significant differences (P<0.01) for individual motility and (P<0.05) for sperm viability. The best results were shown by T2 treatment Conclusion, the addition of Allium cepa extract antioxidant in Ringer's dextrose diluent can maintain the quality of spermatozoa Gallus d